(untitled) (Agro Productividad, 2021)
Objectives: To characterize the supply chain of vanilla (Vanilla planifolia Andrew) in order to detect areas which could be improved and to determine the economic viability of its production. Design/Methodology/Approach: The information was compiled through semi- structured interviews in a vanilla company. The Value Stream Mapping technique was used to describe the supply chain. Additional databases were consulted in order to obtain information on the production and commercialization of vanilla. The economic viability of vanilla production was analyzed with IRR. Results: This case study had five phases in its supply chain. The IRR of cash flow in the traditional and technological production systems were positive, although the IRR of the traditional system was greater even though it had lower production volumes. Study Limitations/Implications: It was observed that vanilla requires between 3 and 4 years for its first harvest, independently of the production system, traditional or technological, which means that there are negative cash flow numbers during the first two years in both systems, despite a positive IRR. Findings/Conclusions: The critical stage in the supply chain of the company studied was the production. The cash flow for the technological system was superior when compared to the traditional system. However, the IRR for the technological system was lower, since the investment in shade cloth was not compensated by the discounted cash flows that could otherwise be obtained.